Nutritional Study of Various Cow Breeds from Bhatta Chowk Lahore (Punjab), Pakistan - Asad Gulzar; Bisma Sher; Shabbir Hussain; Abdul Ahad Rasheed; Muhammad Salman; Shazma Massey; Abdur Rauf (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2023)
The present study was conducted to investigate the nutritional study of cow's milk of various breeds from Bhatta Chowk Lahore. Different cow breeds were found to possess variable amounts of nutritional contents, i.e., highest moisture and ash in the Cholistani cow, highest fat in the Sahiwal cow, highest calcium and specific gravity in the Holstein cow and highest contents of protein, solid-not-fat and total solid in Red Sindhi. Red Sindhi cow’s milk was found to be more nutritious in terms of its richness in proteins, solid-not-fat and total solids whereas Holstein cow was rich in calcium. Calcium was found to be in a range of 550 to 630 ppm with the decrease of concentration in the following order: Sahiwal>Holstein Frisian= Red Sindhi>Cholistani. The Cholistani cow milk showed the presence of 3.126 % protein, 3.5 % fat, 88.2 % moisture, 8.3 % solids-not fat, 11.8 % total solids, 0.791 % ash, 30.5o lactometer reading and 1.0305 kg/m3 specific gravity. Sahiwal cow milk showed 3.318 % of protein, 4.1 % fat, 87.5 % moisture, 30.1o lactometer reading, 1.03 kg/m3 specific gravity, 8.4 % solids-not-fat, 12.5 % total solids and 0.79 % ash. Holstein Frisian’s milk demonstrated the presence of 3.33 % protein, 3.8 % fat, 87.35% moisture, 31o lactometer reading, 1.03 kg/m3 specific gravity, 8.85 % solids-not-fat, 12.65 % total solids and 0.77 % ash. Red Sindhi’s milk revealed the presence of 3.38 % protein, 3.95 % fat, 85.65 % moisture, 28o Lactometer reading, 1.028 kg/m3 specific gravity, 10.4% solids-not-fat, 14.35% total solids and 0.705% ash.